Influence of Structure on Catalytic Properties of La0.7Sr0.3BO3 (B = Mn, Fe, Ni) Perovskite Catalysts in Total Oxidation Reaction of M-Xylene - Tran, Thi Thu Huyen; Tran, Thi Luyen; Nguyen, Thi Tuyet Mai; Dang, Thi Minh Hue; Nguyen, Thi Lan (JST: Engineering And Technology For Sustainable Development, 2021)
The perovskite - type complex oxides of La¬0.7Sr0.3BO3 (B = Mn, Fe, Ni) were prepared, studied of catalytic activity and kinetic in total oxidation reaction of m-xylen in our previous reports. Results showed that perovskite phases can be perfectly crystallized at the temperature of 600oC and they have good catalytic activity and low activation energy in total oxidation reaction of m-xylen. The reaction of total oxidation of m- xylene on the La¬0.7Sr0.3BO3 (B = Mn, Fe, Ni) catalysts occurs mainly in the low temperature range (200-300oC ), so the amount of adsorbent oxygen on the catalyst is an important factor affecting the catalytic properties of this material system. In this report, we continue studying the influence of structure on catalytic properties of La¬0.7Sr0.3BO3 (B = Mn, Fe, Ni) catalysts in total oxidation reaction of m-xylen based on the measurable results of crystal structure analysis by Rietveld analysis method, infra-red spectroscopy and temperature - programmed desorption of oxygen. Obtained results show that between structure and catalytic properties of catalyst have a close relationship: the more structural distortion in perovskit occurs, the greater of the amount of adsorbent oxygen and the link B-O of catalysts is the less durable, the higher of catalytic activity in total oxidation recation of m-xylene.